P12.08 Efficacy of trazodone slow release in insomnia associated with high-dose steroid therapy in neuro-oncological patients. (9th September 2021) - Botturi, A; Gaviani, P; Redaelli, V; Simonetti, G; Lucchiari, C; Silvani, A
Abstract: BACKGROUND: Insomnia linked to therapeutical intake of intravenous (IV) megadoses of steroid (Mgds, 8–16 mg) is a common side effect in neuro-oncology patients. Hypno-inducing drugs (IP) and Benzodiazepines (BDZ) can provoke drug interference and daytime sedation. Trazodone (Trz) is an atypical antidepressant with poor liver metabolism; it has moderate histamine-1 (H1) receptor antagonism and possesses some anxiolytic and hypnotic properties. We tested the use of the Trz retard (RP) formulation as a hypnotic drug in patients undergoing a therapeutic regimen with IV Mgds. To evaluate anxiety and side effects. MATERIAL AND METHODS: 10 patients (6 females and 4 males) admitted to the Neuro-oncology Department of the Neurological Institute "Carlo Besta" treated with Mgds IV. The average age was 55 years and the mean HAM-A score was 25. Instruments included the Hamilton Anxiety Scale (HAM-A), the Clinical Global Impression (CGI), and the Pittsburgh Sleep Quality Index (PSQI). Trz RP was administered at a dosage of 25-50-75 mg/day in the evening. RESULTS: All 10 patients reported improved hypnotic profiles within the third day of Trz RP administration. Four patients improved on the first day. Reduction of the HAM-A score was found on the third day. No adverse events (epilepsy, daytime sedation, incontinence) were observed in 3 weeks. CONCLUSIONS: Trz RP proved to have a swift beneficial effect on sleep and anxiety without side effects in the short term. Trz may be preferred to IP and BDZ in patients receiving IV Mgds, considering the lack of daytime sedation and the reduced pharmacological inference. Larger samples will enable future research to better describe the characteristics and the indication of Trz.